KEBIJAKAN PEMERINTAH INDONESIA DALAM PENANGANAN COVID-19 - Ikmal, Novita Maulida; Noor, Machdian (JURNAL LITBANG PROVINSI JAWA TENGAH, 2021)
Throughout 2020 the world has been shocked by the emergence of a new virus that is infecting the world today, namely Coronaviruses (CoV). The virus has the scientific name SARS Cov 2. The COVID-19 pandemic has also had a considerable impact on investment, which makes people choose to be very careful in buying goods and even investing. The government also urges the public to implement social distancing, such as working from home, and worshiping from home. This study uses policy analysis theory to reveal government policies in dealing with the community's economy. The writing of this article is a library research with a qualitative method which is to explain something based on the data and numbers narrated in the sentence. The results of this study reveal various policies implemented by the government as an effort to suppress the spread of COVID-19, including preventive, promotive and social safety net policies. In addition, the government is also trying to ease the community's economy due to the COVID-19 pandemic with the establishment of the Family Hope Program, Non-Cash Food Assistance, Pre-Employment Cards, Electricity Subsidy Assistance. The government also budgets allocation funds and provides credit relief for informal sector workers and UMKM actors.